2021
DOI: 10.1038/s41597-021-00845-7
|View full text |Cite
|
Sign up to set email alerts
|

The DecNef collection, fMRI data from closed-loop decoded neurofeedback experiments

Abstract: Decoded neurofeedback (DecNef) is a form of closed-loop functional magnetic resonance imaging (fMRI) combined with machine learning approaches, which holds some promises for clinical applications. Yet, currently only a few research groups have had the opportunity to run such experiments; furthermore, there is no existing public dataset for scientists to analyse and investigate some of the factors enabling the manipulation of brain dynamics. We release here the data from published DecNef studies, consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Multivoxel Pattern Analysis (MVPA) is considered a promising technique that introduces machine learning into the field of psychology, currently used to study information contained in distributed neural activity patterns to infer the functional roles of brain territories and networks ( Mahmoudi et al, 2012 ). In application, based on MVPA, neural feedback decoding (DecNef) can be performed for identified brain activity patterns, guiding clinical interventions for mental illnesses ( Cortese et al, 2021 ). Currently, neuroregulation techniques based on brain activity pattern decoding mainly include invasive and non-invasive techniques ( Temel et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multivoxel Pattern Analysis (MVPA) is considered a promising technique that introduces machine learning into the field of psychology, currently used to study information contained in distributed neural activity patterns to infer the functional roles of brain territories and networks ( Mahmoudi et al, 2012 ). In application, based on MVPA, neural feedback decoding (DecNef) can be performed for identified brain activity patterns, guiding clinical interventions for mental illnesses ( Cortese et al, 2021 ). Currently, neuroregulation techniques based on brain activity pattern decoding mainly include invasive and non-invasive techniques ( Temel et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…NFT researchers may wish to examine the value of these approaches for heightening internal and external validity of EEG-based NFT. In a similar vein, fMRI-based NFT has increasingly relied on multivariate decoding methods (Taschereau-Dumouchel et al, 2021), and the potential of these advanced methods has shown promise for basic science and applied research alike (Cortese et al, 2021; Z. Wang et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…The DecNef Collection: A database regrouping the data of multiple previous decoded neurofeedback experiments (https://bicr-resource.atr.jp/drmd/) (Cortese et al, 2021).…”
Section: Related Resourcesmentioning
confidence: 99%